2009
DOI: 10.1161/strokeaha.108.540492
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Independently Predicts the Development of Ischemic Stroke in a Taiwanese Population

Abstract: Background and Purpose-Of few prospective studies that have focused on the relationship between fibrinogen and ischemic stroke (IS) in Asian populations, the findings were inconsistent with those conducted in Western countries. Therefore, we aimed to investigate the temporal relationship between fibrinogen levels (plus several related parameters) and IS in a community-based study in Taiwan. Methods-Baseline data from 3281 adults (Ն20 years of age) in the Cardiovascular Diseases Risk Factor Two-Township Study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 47 publications
5
57
0
1
Order By: Relevance
“…Patients with lacunar showed moderated elevation of fibrinogen. Consistent with our results, Chuang et al (2009) reported that fibrinogen independently predicted future ischemic stroke risk. Elevated fibrinogen tended to be more strongly associated with NLS than LS (HR = 1.40; 95%CI = 1.09 to 1.80; P = 0.029).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Patients with lacunar showed moderated elevation of fibrinogen. Consistent with our results, Chuang et al (2009) reported that fibrinogen independently predicted future ischemic stroke risk. Elevated fibrinogen tended to be more strongly associated with NLS than LS (HR = 1.40; 95%CI = 1.09 to 1.80; P = 0.029).…”
Section: Discussionsupporting
confidence: 92%
“…It was revealed that plasma fibrinogen level was significantly associated with coronary heart disease (CHD), stroke, and other causes of vascular and non-vascular mortality (Chuang et al, 2009;Chen et al, 2013). Unfortunately, very few studies report different risk of elevated fibrinogen between LS and NLS.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma fibrinogen levels were determined at day 1 and day 5 of the onset of ischemic stroke as presented at Fig (1).Three main risk factors of ischemic stroke were examined, the most prevalent risk factor was hypertension 22 (73.3%) followed by dyslipidemia 19 (63.3%) followed by DM 13 (43.3%). The association between the risk factors and Fibrinogen levels at day 1 and 5 are presented at Tables (1)(2). Stroke severity at day 1 and 90 of ischemic stroke were determined by NIHSS are presented at Fig (2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hypertension and diabetes, fibrinogen independently predicts future ischemic stroke risk [2]. Fibrinogen also acts as an acute-phase protein and increases after stroke [3].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although current smoking was found to be a risk factor in previous Taiwanese hospital-based studies, it was not significantly associated with the risk of ischemic stroke in a longitudinal, community-based study. 2 In China, a marginal association between smoking and risk of stroke was found in stroke patients from 36 hospitals (38.8% and 33.3% for cases and controls, respectively). 3 More quality research on the risk factors for stroke, such as smoking, in the Chinese population is therefore warranted.…”
Section: To the Editormentioning
confidence: 99%